Devil's gulch [large type] - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Devil's Gulch Western ;, 2023)
"John Holt is a traveling gunslinger. He's been liberating dirty towns west of the Mississippi of murdering outlaw trash ever since the Civil War ended. No questions asked. Payment on demand. The only way out of this town is in a pinewood box. Holt's latest job is in Devil's Gulch in Colorado Territory. But wiping out bands of bank robbers is just the beginning. More disorder is brewing, and the skittish mayor has handpicked Holt as the new sheriff. Holt is what the town needs: a mercenary with a badge, a loaded Remington, and a deadeye-aim for trouble. Devil's Gulch has the vigilance committee. The man behind it--Joe Mullen, the largest rancher and mine owner in the valley--isn't keen on an outsider like Holt muscling in on a good thing. Mullen already has his hand in all the crime in Devil's Gulch. He also triggers it. He likes keeping things wild. With the barbaric Bostrom brood under his command, he's hoping it stays that way. Holt quickly finds himself on familiar ground: up against cutthroats on the other side of the only law that counts. Holt's law. Devil's Gulch is his town now. And he's itching to clean it till it sparkles"--